(untitled) (Research, Society and Development, 2024)
Introduction: Information systems are tools that contribute to improving the quality and productivity of health care, where the data made available make it possible to carry out research and teaching activities. Objective: To map databases and health information systems in Brazil, with an emphasis on access, quality, gaps, limitations, challenges, opportunities for improvement and improvement. Method: Scope Review, with a time frame from 2019 to 2023. Results: Seventeen studies were retrieved, eleven cross-sectional studies, two bibliographic reviews, one systematic review, one ecological study, one case-control and one observational cohort study. Conclusion: The studies highlight the need for specific interventions to improve health records, proposing the implementation of efficient information flows, professional training, data standardization and manager awareness.